2019
DOI: 10.1088/1361-648x/ab347a
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric properties of 1 T monolayer pristine and Janus Pd dichalcogenides

Abstract: In this paper, we investigate the stability and thermoelectric properties of 1 T PdSSe, PdSTe and PdSeTe Janus structures using density functional theory (DFT). All three systems are narrow gap semiconductors with indirect bandgaps of 0.94 eV, 0.33 eV and 0.34 eV respectively. Compared to transition metal dichalcogenide (TMD) monolayers, PdS 2 and PdSe 2 are semiconductors with wider indirect bandgaps of 1.29 eV and 0.69 eV respectively. Phonon dispersion calculations demonstrate that all pristine and Janus st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
11
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 87 publications
5
11
1
Order By: Relevance
“…Figure e shows the phonon dispersion of α-Te. The maximum phonon frequency corresponds to an energy of 23 meV, smaller than most of the 2D materials due to the heavy atomic mass of Te, but is comparable to other low κ L systems. The low phonon frequency renders a low Debye temperature for α-Te.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Figure e shows the phonon dispersion of α-Te. The maximum phonon frequency corresponds to an energy of 23 meV, smaller than most of the 2D materials due to the heavy atomic mass of Te, but is comparable to other low κ L systems. The low phonon frequency renders a low Debye temperature for α-Te.…”
Section: Resultsmentioning
confidence: 94%
“…On the other hand, TMDs often have thermal conductivities, too high for good thermoelectrics. In parallel with the experimental study, theoretical calculations, typically involved with simplifications on an electronic band structure and a scattering rate, have been carried out to explore the TE promise of many 2D materials including MX 2 (M = Mo, W; X = S, Se), MCO 2 (M = Ti, Zr, Hf), TiS 2 , ZrS 2 , TiS 3 , black phosphorene, PdXY (X, Y = S, Se, Te), , and Bi 2 Te 2 X (X = S, Se, Te), to name a few. The results of these calculations do not yield ZT values above unity due to a low power factor and/or high thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, Pd pristine was not given much consideration, in particular PdS2 monolayer. We have only considered 1T PdS2 structure because of, very recently published work showing that, in the nonappearance of the spin-orbit coupling (SOC), PdS2 is semiconductor with significant bandgap [6]. The literature has conveyed various materials properties of layered PdS2 monolayer on the photonic and photoelectric fields, i.e., Wang et al, estimated the hole carrier mobility of PdS2 monolayer is ~ 339 cm 2 V -1 s -1 in the X-Dir in year of 2015 [7].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is observed that Figure of merit (ZT) can be enhanced in the Janus PtSSe monolayer under compressive strain [14]. In addition, the Figure of merit in Janus Pd‐dichalcogenides structures have been found larger than their corresponding pristine PdX 2 (X = S, Se) monolayers using density functional theory [15]. Besides, Hoat et al [16] have been found that the n‐type doping can be more favorable for the high‐thermoelectric performance of the HfSSe Janus monolayer.…”
Section: Introductionmentioning
confidence: 99%